BEYOND PROFIT: HOW BMT NU JAMBESARI EMPOWERS MSMES THROUGH SHARIA FINANCING - Fawaid, Fawaid (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study aims to evaluate the effectiveness of sharia financing carried out by BMT NU Jambesari in empowering UMKM actors and building the economic welfare of the community. The research uses a descriptive qualitative method with data collection through interviews, observations and documentation. he novelty of the research lies in the analysis of the role of BMT NU from the perspective of sharia economic law, especially in terms of compliance with sharia principles and its impact on economic sustainability. Sharia financing distributed by BMT NU Jambesari significantly increases production capacity, increases income, and expands the market. Mentoring and training are carried out to ensure the sustainability of customer businesses. Thus, effective sharia financing that is in accordance with sharia principles can empower UMKM and improve the economic welfare of the people. Keywords: sharia financing, empowerment of UMKM, people's economy